2008
DOI: 10.1002/jqs.1198
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐millennial climate shifts in the western Mediterranean during the last glacial period recorded in a speleothem from Mallorca, Spain

Abstract: 2008. Sub-millennial climate shifts in the western Mediterranean during the last glacial period recorded in a speleothem from Mallorca, Spain.ABSTRACT: Very few high-resolution and directly dated terrestrial archives of the last glacial period exist for the western Mediterranean region, yet this is a key locality for recording sub-millennial North Atlantic and Mediterranean climate change. Here, we present evidence of effective precipitation changes based on growth history and d 13 C of calcite in a Mallorcan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…During glacials, cool SSTs in the North Atlantic decreased the energy budget over the ocean and the moisture uptake in winter. This resulted in drier conditions in the western Mediterranean (Daniau et al, 2007;Dumitru et al, 2018;Hodge, Richards, Smart, Ginés, & Mattey, 2008;Moreno et al, 2005).…”
Section: Climate Variability On Millennial Timescalesmentioning
confidence: 99%
See 1 more Smart Citation
“…During glacials, cool SSTs in the North Atlantic decreased the energy budget over the ocean and the moisture uptake in winter. This resulted in drier conditions in the western Mediterranean (Daniau et al, 2007;Dumitru et al, 2018;Hodge, Richards, Smart, Ginés, & Mattey, 2008;Moreno et al, 2005).…”
Section: Climate Variability On Millennial Timescalesmentioning
confidence: 99%
“…Concomitantly, the AMOC has a large impact on sea surface temperatures (SST) in the North Atlantic (Pailler & Bard, 2002) as well as the western Mediterranean Sea (Bagniewski et al, 2017;Martrat et al, 2004). Changes in SST and the position and topography of the ice sheets, in turn, have an impact on the atmospheric circulation (Cacho et al, 2000;Merz et al, 2015;Moreno et al, 2005;Naughton et al, 2009) by influencing the pathways of North Atlantic storm tracks and the position of the Intertropical Convergence Zone (ITCZ; Naughton et al, 2009;Stríkis et al, 2018) and, as a consequence, on effective precipitation in the Mediterranean (Hodge, Richards, Smart, Andreo, et al, 2008;Hodge, Richards, Smart, Ginés, & Mattey, 2008). A decrease or even shutdown of the AMOC is coupled to lower SSTs in the North Atlantic and a southward shifted oceanic thermal front, which results in a more southerly route of the Atlantic jet stream and its associated westerlies (Naughton et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Carbon isotope composition has also emerged has an interesting proxy for effective precipitation, as the contribution of isotopically 13 C-depleted CO 2 from soil decreases when effective precipitation declines (e.g. Genty et al, 2003;Hodge et al, 2008) or, in some cases, simply changes the residence time of water in the soil (e.g. Bar-Matthews et al, 2000;Frisia et al, 2006).…”
Section: Speleothem Isotope Recordsmentioning
confidence: 99%
“…rough terminus post quem for upper PA aggradation during MIS 3. This corresponds to a late Pleistocene period for which records of Mediterranean paleoclimates document frequent shifts between interstadial and stadial climates that brought about contrastive, rapidly alternating warmer and moist or arid and cold conditions (e.g., Allen and Huntley, 2000;Burjachs and Allué, 2003;Hodge et al, 2008). Therefore, at least in the case of the local situation in the Río Seco tributary it can be concluded that a relationship exists between effective downcutting, intense geomorphic sediment transfer, and a Pleistocene period with frequent shifts between stadial and interstadial climates.…”
Section: Pleistocene Aggradation and Degradationmentioning
confidence: 96%